EXPLORING LANGUAGE INTERFERENCES: SLOVAK LEARNERS OF SPANISH AND THE CHALLENGES IN PAST TENSE USAGE - Mária Spišiaková; Nina Mocková; Наталя Вікторівна Шумейко (Novìtnâ Osvìta, 2023)
Different linguistic classifications of Spanish and Slovak make the differences between these two languages. The genetic criterion classifies languages, clustering them into language families, the largest among which is the Indoeuropean one. The typological criterion divides languages according to their grammatical structures. Meanwhile, Slovak is genetically a Slavonic language, and Spanish is a Romance language. Therefore, they both belong to different language families. Also, according to the typological criterion, Slovak is a synthetic language, and Spanish is an analytic language. Based on a theoretical study of the standard features and differences between the Slovak and Spanish verb systems, we formulated the hypotheses about language interferences, which are accepted or rejected at the end of the research. The current research aims to examine the errors in the use of past tenses by Slovak university students who study Spanish as a foreign language, and then analyze where these errors are due to interference with their native language. The present paper observes what errors students make in using past tenses in Spanish. The research question is: What interferences do Slovak learners of the Spanish language experience in the use of past tenses? We applied scientific methods (an observation, a textual analysis, a synthesis) to conduct the study. The first method was an observation. Applying this method made it possible to gather data by watching the process of doing grammatical exercises in Spanish during classes held from September 2020 to May 2022 for the first- and second-year students at the Faculty of Applied Languages of the University of Economics in Bratislava. These students knew English and were generally better at it than Spanish. We also conducted a textual analysis that primarily looked at the learners’ short-text writing skills. We used a form with 30 phrases the respondents needed to complete using past tenses. Then, we assessed the written and spoken communication skills of students. The analysis results show that, on the one hand, most respondents needed help distinguishing between the past continuous and simple past tenses, resulting in misuse. On the other hand, we found some slight errors in phrases in which the present perfect tense was supposed to be used.